Ghrelin ameliorates pancreaticobiliary inflammation and associated remote organ injury in rats - YEGEN, BERRAK (WILEY, 2006)
The present study was designed to evaluate whether ghrelin could reduce organ injury and systemic inflammation induced by pancreaticobiliary obstruction. In Sprague-Dawley rats, either the bile duct (BDL) or common pancreaticobiliary duct (PBDL) was ligated or a sham operation was applied. BDL or PBDL rats received either ghrelin (10 ng/kg) or saline intraperitoneally immediately before the surgery and once a day until the rats were decapitated at 72 h. The pancreas, liver, lung and kidney were removed for the histological analysis, and for the determination of malondialdehyde (MDA), glutathione (GSH) levels and myeloperoxidase activity (MPO). MDA and MPO levels in all the tissues, which were elevated in PBDL group (p < 0.05-0.001), were reversed back to control levels in ghrelin-treated rats. In BDL group, elevations in hepatic MDA and MPO levels (p < 0.001) were also abolished by ghrelin treatment. In contrast to saline-treated group with severe pancreatic damage, ghrelin-treated rats demonstrated a moderate pancreatic and hepatic destruction accompanied with reduced pulmonary and renal damages. The results illustrate that ghrelin protects the hepatic and pancreatic tissues, as well as remote organs against oxidative injury, by a neutrophil-dependent mechanism. (c) 2006 Elsevier Ireland Ltd. All rights reserved.
Keywords: myeloperoxidase; cholestatic hepatic injury; acute pancreatitis; lipid peroxidation; OXIDATIVE STRESS; ACYLATED PEPTIDE; VITAMIN-E; ACTIVATION; HORMONE; PANCREATITIS; GLUTATHIONE; RECEPTOR; MYELOPEROXIDASE; CHOLESTASIS